Trends in Cesarean Section in a Tertiary Referral Hospital: Time-Series Analysis (Central Asian Journal of Medical Sciences, 2025)
Objectives: To analyze the causes and indications of C-sections conducted at the tertiary referral center and to forecast future patterns. Methods: We retrospectively analyzed 25,311 delivery records from 2013 to 2022 at the National Center for Maternal and Child Health, Mongolia. All C-sections from 22 weeks’ gestation onward were included. Data were collected using a structured questionnaire form including maternal, obstetric history, surgical indications, and other influencing factors. Causes of C-sections were identified through descriptive statistics, logistic regression, and ARIMA time-series modeling. Statistical analysis was performed using Stata BE 18.0, with p < 0.05 considered significant.  Results: The mean gestational age was 38.1±2.09 weeks, the 88.4% of pregnancies were term deliveries, and 42.6% were emergency C-sections. The most common indications for C-section were previous C-section, maternal comorbidity, severe preeclampsia, and fetal distress. According to time-series analysis, despite of no significant change in the C-section rate during the study period, the trends in C-sections are growing. The percentage of nulliparous women in total C-sections is likely to increase by 0.81% per year. In 2030, the percentage of C-sections will reach 35.5%, whereas the percentage of emergency C-sections in total C-sections will reach 59.5%. Conclusions: C-sections for nulliparous women were mainly due to failed birth induction, failed labor stimulation, and fetal distress. It is estimated that the percentage of C-sections in total births will increase by 0.02% annually, reaching 35.5% by 2030.